Genetic relationships of populations of the Black Kite Milvus migrans (Accipitriformes: Accipitridae) in the east of its range in Asia and Australia - Andreyenkova, Natalya G.; Hong, Shiao-Yu; Lin, Hui-Shan; Iwami, Yasuko; Kirillin, Ruslan A.; Literák, Ivan; Zhimulev, Igor F.; Karyakin, Igor V. (Zootaxa, 2024)
While the Black Kite Milvus migrans is one of the most widespread birds of prey, occurring over Eurasia, Africa and Australia, it remains poorly understood outside of Europe, with southeast Asian populations particularly mysterious as their taxonomy is based on outdated morphological data. The subspecies M. m. formosanus, described in 1920, is thought to inhabit Taiwan and Hainan; however, populations in these areas have experienced dramatic changes over the past fifty years. Furthermore, M. m. formosanus is the only officially recognised subspecies for which almost no genetic data is yet available. Based on two mitochondrial genes, we compared Taiwanese Black Kites with northeast Asian and Japanese M. m. lineatus, Indian M. m. govinda and Australian M. m. affinis to reconstruct details of their population history. While Indian and Australian Black Kites are descendants of the same population, they do not share common haplotypes, probably having diverged by the end of the last glaciation. The Japanese population is distinctive in showing genetic uniformity, and it may be isolated from the mainland population. Nesting Taiwanese kites carry two previously known M. m. lineatus haplogroups and a new haplogroup possibly inherited from M. m. formosanus previously occurring in the area. A recent decline in the local population, along with expansion of M. m. lineatus, most likely led to Taiwan now being inhabited by descendants of both subspecies, which form two genetically isolated populations in southern and northern Taiwan.